THE FUTURE OF TRADE AND INVESTMENT RELATIONS BETWEEN CENTRAL ASIA AND THE UNITED STATES (International journal of artificial intelligence, 2026)
This article examines the future of trade and investment relations between Central Asia and the United States, highlighting economic opportunities, structural challenges, and geopolitical considerations. Central Asia, comprising Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, offers abundant natural resources, strategic geographic positioning, and emerging markets that present significant potential for U.S. engagement. The study discusses historical trends, sectoral investment patterns, regional integration initiatives, and governance issues that influence bilateral economic cooperation. Furthermore, it emphasizes the importance of sustainable investment practices, adherence to Environmental, Social, and Governance (ESG) criteria, and alignment with regional connectivity projects. The analysis reveals that effective collaboration requires addressing institutional inefficiencies, promoting transparency, and fostering public-private partnerships, while navigating competition from other global powers. Ultimately, the study provides a forward-looking framework to strengthen mutually beneficial trade and investment relations, ensuring long-term economic growth, regional stability, and technological development.